The Influence of Financial Literacy on MSME Business Performance : JEL Classification: G53, G21, L26, M21, O16 - Sitti Ainung Anugrawati Sari; Imaduddin; Juliyanty Sidik Tjan (Journal La Bisecoman, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in Indonesia’s economy through job creation, income generation, and regional development. However, challenges such as limited financial management skills and restricted access to financial services often hinder their performance. Financial literacy and financial inclusion are considered key factors in improving MSME business performance. This study employed a quantitative approach with a non-experimental design. Data were collected from 51 MSMEs assisted by the UPT PLUT South Sulawesi using purposive sampling. The criteria included business owners with at least two years of experience. Data collection techniques included questionnaires, observation, and literature review. Data were analyzed using multiple linear regression supported by validity, reliability, and classical assumption tests with SPSS. The findings indicate that financial literacy has a positive and significant effect on MSME business performance, with a regression coefficient of 0.678 and a significance value of 0.000. In contrast, financial inclusion shows a positive but insignificant effect, with a coefficient of 0.124 and a significance value of 0.299. These results suggest that internal capabilities, particularly financial knowledge and skills, play a more dominant role than access to financial services. Financial literacy significantly enhances MSME performance by improving financial management, decision-making, and business sustainability, while financial inclusion requires further optimization to produce a stronger impact.